Arrhythmic Risk Stratification in Patients with Arrhythmogenic Cardiomyopathy - Marisa Varrenti; Eleonora Bonvicini; Leandro Fabrizio Milillo; Ilaria Garofani; Marco Carbonaro; Matteo Baroni; Lorenzo Gigli; Giulia Colombo; Federica Giordano; Raffaele Falco; Antonio Frontera; Roberto Menè; et al. (Diagnostics)
Arrhythmogenic cardiomyopathy is a heart disease in which the heart muscle is replaced by scar tissue. This is the main substrate for the development of malignant ventricular arrhythmias. Sudden cardiac death is the most common manifestation and can often be the first sign of the disease, especially in young people. Correct stratification of arrhythmic risk is essential for the management of these patients but remains a challenge for the clinical cardiologist. In this context, the aim of our work was to review the literature and to analyse the most important studies and new developments with regard to the stratification of the risk of arrhythmia in patients suffering from arrhythmogenic cardiopathy.